Immuno- and gene expression analysis of EGFR and Nestin during mice skin development - Falodah, Fawaz Adnan; Al-Karim, Saleh (Tissue & cell, 2016)
Skin stem cell populations reside in the adult hair follicle, sebaceous gland, dermis and epidermis. However, the origin of most of the stem cell populations found in the adult epidermis is still unknown. Far more unknown is the embryonic origin of other stem cells that populate the other layers of this tissue. The main objectives of the present study were to identify the precise anatomical localization of stem cells in mice during skin developing; and to determine the expression levels by using immuno- and gene expression analysis. In this comparative cross sectional study, six ages been chosen and divided into: embryonic days (E12.5, E14.5 and E19.5) and litter days (L7, L14 and L19). Skin were removed from the back side and processed to assess both immuno- and gene-expression of EGFR and Nestin surface antigen markers. Data of the different studied age groups was compared using the SPSS software. EGFR was mainly expressed in the outer root sheath (ORS), in basal and, to a lesser extent, in suprabasal keratinocytes and tend to lie where the dermis comes closest to the skin surface, while Nestin expressed throughout the dermis in the early embryo, but it is subsequently restricted to the follicular connective tissue sheaths later in development and to hair follicles after birth. Immunoexpression analysis showed a strong EGFR expression in all group ages except E12.5 which recorded as moderate, while Nestin showed strong expression level for all embryonic stages, while in the litters it was moderate. The qRT-PCR results were consistent with those of the immunohistochemical study. The Pearson correlation analyze present a correlation between the cases of study with age (p≤0.01), which indicated to the effect of age to mice development. EGFR and Nestin showed to have vital role during mice development, and considered to be suitable markers for the study of skin stem cells.